Oil Price and Industrial Growth in Saudi Arabia: Sectoral and Asymmetry Analyses - Mahmood, Haider (International Journal of Energy Economics and Policy, 2021)
Oil price could have long-lasting effects on any oil-exporting economy due to its dependence on oil revenue. This present research probes the role of Oil Price (OP) on the 22 categories of manufacturing industries of Saudi Arabia and the growth of total industries during 1990-2018 in the nonlinear settings. To serve the purpose, we utilize the unit root test and nonlinear cointegration test of Shin et al. (2014) based on modified bound statistics of Kripfganz and Schneider (2019). The increasing or decreasing oil price could have different magnitude or direction of effects. Hence, the present research applies a nonlinear cointegration in the relationship between oil price and industrial growth. We found cointegration in the total industries’ model and 19 industries’ models. In the long run, increasing OP has a positive relationship with 8 out of 22 investigated industries and has a negative relationship with 2 out of 22 investigated industries. Decreasing OP has a positive relationship with 2 out of 22 industries and has a negative relationship with 4 out of 22 industries. In the short run, increasing OP has a positive relationship with one industry and has a negative relationship with 10 out of 22 investigated industries. Decreasing OP has a positive relationship with 3 out of 22 industries and has a negative relationship with one industry. Asymmetry is corroborated in all investigated models except the petroleum industry in the long run and is validated in all models in the short run. Keywords: Oil price, Manufacturing industries, Asymmetry, Nonlinear cointegration JEL Classifications: Q41, Q43, L60, C22 DOI: https://doi.org/10.32479/ijeep.10922